Politics in southeast Asia democracy or less - Case, William (Routledge, 2002)
This volume provides an introduction to the politics of the five key southeast Asian states - Malaysia, Singapore, Indonesia, Thailand and the Philippines - and is intended as a textbook for undergraduate and graduate students taking courses on this subject. Using a comparative politics and political economy perspective, the author focuses in particular on the degree of democracy in the five countries, arguing that in all the countries considered democracy is, to varying degrees, imperfect. The book synthesises a wide range of scholarship, and presents the material in a concise and accessible way